PANDEMI COVID-19 TERHADAP SEKTOR PARIWISATA NEGERI DI ATAS AWAN DI DESA BENTENG MAMULLU KECAMATAN KAPALA PITU KABUPATEN TORAJA UTARA - Dappa, Saena; Lasut, Jouke J.; Kandowangko, Nicolaas (Universitas Sam Ratulangi, 2021)
Covid-19 has become a global problem and has a huge impact on all sectors of life around the world. Starting from the economic sector, health, education, social, tourism and so on. The steps taken by the government in reducing the number of spread of the Covid-19 virus are social distancing. Social distancing is an attempt by a person not to interact at close range or avoid crowds, wash their hands, and wear masks. This policy is considere effective in reducing the spread of COVID-19.North Toraja Regency is an area famous for the term